A preregistered meta-meta-analysis on the global distribution of Hepatotropic Viruses - Shuaibu Suleiman Adeiza; Md. Aminul Islam; Hauwa’u Umar Mungadi; Abdulmalik Bello Shuaibu; Ranjit Sah (Вопросы вирусологии)
Introduction. Hepatotropic viruses (HAV, HBV, HCV, HDV, and HEV) significantly impact global health, with varying prevalence across regions.